Butoh America Butoh Dance in the United States and Mexico from 1970 to the early 2000s - Calamoneri, Tanya (Taylor & Francis, 2022)
Min Tanaka, American butoh artists, Cultural Studies, experimental art, Kazuo Ohno, Shuji Terayama, Theatre